Ambulatory blood pressure variability measures in hypertensive patients according to non-alcoholic fatty liver disease state. (14th October 2021) - Kakouri, N; Konstantinidis, D; Siafi, E; Tatakis, F; Polyzos, D; Drogkaris, S; Koskinas, J; Thomopoulos, C; Tsioufis, K
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) represents the most frequent cause of chronic hepatic disease and independently determines hypertension and future cardiovascular events. Increased blood pressure variability (BPV) assessed by 24-hour blood pressure (BP) monitoring including mean arterial morning surge have been also associated with increased rates of cardiovascular events. Purpose: To compare different BPV measures in hypertensive patients with and without NAFLD. Methods: Consecutive newly diagnosed untreated hypertensive patients without history of cardiovascular disease underwent clinic and ambulatory BP measurements. NAFLD was diagnosed by liver ultrasound to separate patients into those with and without NAFLD. BPV was derived by assessment of standard deviation (SD) of systolic and diastolic BP (24-h, daytime and nighttime), average real variability (ARV) of systolic and diastolic BP, coefficient of variation (CV) of systolic BP (24-h, daytime), weighted SD (wSD) of systolic BP (24-h, daytime), maximum BP and mean arterial morning surge. Results: Among 146 hypertensive patients (mean age 57±11 years, 64 men, 24-h mean systolic/diastolic BP 140±10/84±9 mmHg) those with NAFLD (n=76) compared to the non-NAFLD group (n=70) were younger (54.7±10.1 vs 58.6±11.2 years, respectively, p=0.03), male gender was more prevalent (42 vs 22 respectively, p=0.004), and body mass index was more increased (33.2±4.1 vs 27.0±3.5 kg/m 2, p<0.001). Moreover, NAFLD patients compared to those without NAFLD were characterized by higher levels of mean arterial pressure morning surge (12.4±8.9 vs 8.7±8.5 mmHg, p=0.03), but the remaining BPV measures were not different between the two groups. NAFLD was a determinant of both diastolic BP ARV (B=0.34, p=0.007) and mean arterial morning surge (B=0.47, p=0.006) after adjustment. Conclusions: Mean arterial pressure morning surge was significantly higher in hypertensive patients with NAFLD compared to their non-NAFLD counterparts, while whole day BPV measures were not increased in NAFLD except for ARV of diastolic BP. Our findings may partially explain the increased cardiovascular risk of comorbid NAFLD in hypertension. Funding Acknowledgement: Type of funding sources: None.